قياس فاعلية الرقابة المالية الداخلية من وجهة نظر مراقبي وزارة المالية في الكويت - سليم، محمد مجيد (جامعة المنصورة - كلية التجارة, 2009)
هدفت هذه الدراسة إلي قياس فاعلية الرقابة المالية الداخلية من وجهة نظر مراقبي وزارة المالية في الكويتية ، حيث تم اعتماد المعيار الأمريكي رقم (78) في تحديد مكونات الرقابة الداخلية وهي بينة الرقابة وتقدير المخاطر والمعلومات والاتصالات وأنشطه الرقابة والمتابعة. وتم استخدام استبانة لجمع المعلومات من 94 مراقبا للحسابات في وزارة المالية، وتوصلت الدراسة إلي عدد من النتائج اهمها انه توجد علاقة ذات دلالة إحصائية بين فاعلية الرقابة المالية الدلالية والبيئة الخاصة بالرقابة ومستوي المخاطر ومستوي المعلومات والاتصالات المتعلقة بالرقابة وحجم ونوعية الأنشطة والإجراءات الرقابية ودرجة المتابعة المتعلقة بالرقابة المتبعة في وزارة المالية. \ كما توصلت الدراسة الي عدد من التوصيات ابرزها، توفير شرح مفصل للمعيار الأمريكي رقم (78) الخاص بالرقابة الداخلية للقائمين علي نظام الرقابة المالية الداخلية في وزارة المالية، عمل دراسة ميدانية تختص بالنماذج والاشكال الخاصة بالتقارير الواجب نوافرها للإدارة العليا والتي تبين عملية متابعة الرقابة المالية الداخلية في وزارة المالية. وعقد اجتماع دوري بين الإدارة العليا في وزارة المالية والقائمين على نظام الرقابة المالية الداخلية وذلك للتعرف علي نوع الانحرافات الموجودة وهل يمكن معالجتها. This study aim is to measure, the efficiency of internal auditing in Kuwaiti ministry of finance, from their viewpoint the study tried to compare the actual practices with that of the requirements of (SAS78) Taking the following points in considerations, control environment, assessment of internal control risks, information and communication system, internal control activities and monitoring and follow up of the internal auditors in the Ministry of Finance. \ A questionnaire was distributed to (94) auditors from the Ministry of Finance. The study used the statistical package SPSS. \ The major findings were that there are statistically significant relationship between the effectiveness of internal financial control and its environment, the level of risk, the level of information and communication, the size, quality and quantity of the activities and actions of regulatory bodies, and monitoring actions of Kuwaiti government the main recommendations are as follows: \ Develop special standards for Kuwaiti government to determine the responsibilities and rights of internal financial controllers. \ Provide a complete explanation of the American standard no (78) \ There is a need to conduct studies on types and content of reports that must be provided to the higher management, showing the process of internal financial control in Kuwaiti government \ The higher management ;(Minister General Manager or Head of Department) must carry on meeting with auditors who are in charge of internal financial control , to know the area of mistakes directly.
Keywords: النظم المحاسبية -- الرقابة المالية -- الكويت -- وزارة المالية -- الرقابة المحاسبية -- الإدارة العامة -- القطاع العام -- الميزانية العامة -- تقييم الأداء -- مراجعة الحسابات -- التقارير المالية -- مراقبو الحسابات